Headache disorders: a persistent public health challenge for the under 50s - Weijian Meng; Weijian Meng; Liutao Sui (Frontiers in Neurology, 2024)
IntroductionCurrently, neurological diseases has surpassed cardiovascular diseases as the primary cause of global disease burden. Among these, headache disorders are the most prevalent and have emerged as the main cause of disability in people under 50 years old in recent years. Since the release of GBD 2021, there has been no comprehensive systematic exposition on the burden of headache among individuals under 50 years old and a forecast for future burdens. This study aims to quantify the global, regional, and national burden of headache disorders among people under 50 from 1992 to 2021 and to predict future trends in order to provide policy makers with precise and effective epidemiological evidence.MethodsThis study extracted the incidence, prevalence, and DALYs data related to headache disorders in the 5–50 age group from the GBD 2021. After age-standardizing the data, we used joinpoint regression analysis and health inequity analysis to analyze the burden and temporal trend of headache disorders and predicted the future disease burden and changes based on the age-period-cohort model.ResultsBy 2021, the case number of global incidence, prevalence and DALYs have increased by 35, 39, and 41%, respectively, over the past 30 years. The incidence and prevalence of tension-type headache (TTH) are significantly higher than those of migraine, but migraine causes greater health burdens. The burden is higher for female than for male. In terms of age, youth aged 25–29 years had the highest incidence in 2021, with an age-standardized rate (ASR) of 13,454.64 (95%CI, 9,546.96–18,361.36) per 100,000 population. Nationally, the highest ASR of incidence and prevalence are found in Norway, and the most damaging to health is found in Belgium. Among the five sociodemographic index (SDI) categories, the middle SDI has the highest number of cases (190 million in 2021). It is worth noting that the forecast shows that by 2046 the three indicators will reach 680 million, 2.33 billion, and 41 million, respectively, indicating that the burden of headache disorders in this age group will continue to persist.ConclusionGlobally, the burden of headache disorders in people under 50 years of age remains significant and has not improved over the past 30 years, especially in regions with high SDI. Headache problems will continue to pose a serious public health challenge for this age group for some time to come. This study reveals the burden and distribution of headache disorders in this age group, providing important basis for governments and policymakers to accurately and effectively allocate health care resources, strengthen prevention and management strategies, and respond to this global health problem.